Comparison of CT findings between pyogenic meningitis and tuberculosis meningitis at a tertiary care Hospital - Asim khan; Wajiha Rizwan; Ayesha Akram; Bilal Zafar; Khaver Ali (Journal of University Medical & Dental College, 2026)
BACKGROUND & OBJECTIVES: Early detection and management of tuberculous meningitis can improve its prognosis. TBM and pyogenic meningitis (PM) have overlapping clinical presentations. The objective of this study was to determine the frequency of TBM and PM among children with meningitis and to compare their CT findings. METHODOLOGY: This study was conducted in the Department of Paediatrics, The Children’s Hospital, Lahore, from 1st January to 31st June 2025. A total of 94 children aged 4 months to 14 years who fulfilled the diagnostic criteria for TBM or PM were included. After informed consent, contrast-enhanced CT scans were performed and assessed for basal enhancement, hydrocephalus, infarction, and intracranial tuberculoma. Data were analyzed using SPSS version 20. Chi-square test was applied, with p < 0.05 considered significant. RESULTS: Among the study population, 49 children (52.1%) had PM and 45 (47.9%) had TBM. Basal enhancement was more frequent in TBM (77.8% vs 51.0%, p = 0.020). Hydrocephalus (55.6% vs 32.7%, p = 0.012), infarction (42.2% vs 22.4%, p = 0.018), and intracranial tuberculomas (35.6% vs 10.2%, p = 0.001) were also significantly higher in TBM. CONCLUSION: CT imaging is a useful tool to differentiate TBM from PM in children. Findings such as basal cisternal enhancement, hydrocephalus, infarction, and tuberculomas support the diagnosis of TBM and can facilitate early recognition and treatment in resource-limited environments.